Inaccuracies of Measuring Methods and Their Influence on the Regression Function. (1984) - Sauer, W.
Abstract : The quality parameters of electronic components and devices usually depend on the parameters of the materials. In many cases one does not know the theoretical relationship between the parameters, and therefore one makes technological experiments and measures the values of the parameters. Usually it is necessary to take several measuring points and calculate from this the unknown relationship between the parameters. The simplest equation that one can use is the linear function. In this case the theoretical probability density function is a Gaussian-function. Otherwise it is necessary to assume that the linear function is an approximation. When the measuring process has an inaccuracy, then one can show that the increase of the linear function is smaller and it is necessary to estimate a factor of correction to calculate the theoretical or exact relationship.